Impact of guidelines on antibiotics prescription for community-acquired pneumonia - Rojas, Elsa M.; Rueda, Zulma V.; Aguilar, Yudy A.; Vélez, Lázaro A. (Iatreia, 2008)
PREVIOUS PRESENTATION: This study was presented in part at the 47th Interscience Conference on Antimicrobial Agents and Chemotherapy (ICAAC); September 17, 2007; Chicago, Ill.CONFLICT OF INTEREST STATEMENT: Lázaro Vélez has received research funding from Astra-Zeneca and Roche Colombia, and has been a consultant for Pfizer. Other authors did not declare conflicts of interest.BACKGROUND: Community Acquired Pneumonia (CAP) is an important reason to prescribe antibiotics in hospitals. Since etiologic diagnosis is cumbersome, most clinicians use initial broad coverage as suggested by local/international guidelines. This approach may induce overprescription of antibiotics, increasing costs, resistance and adverse effects. Our aim was to quantify the impact that overprescription of antibiotic has on the implementation of IDSA/ATS 2007 guidelines.METHODS: A prospective cohort study conducted at 11 hospitals in Medellín, Colombia, 2005-06. We included 205 adult CAP patients with an identified pathogen. Four categories of appropriateness were established: appropriate, insufficient, excessive and useless. To quantify the magnitude of antibiotic prescription, we compared the Defined Daily Doses (DDD) of antibiotics suggested for the empiric treatment by IDSA/ATS 2007 guidelines according to severity (mild, moderate and severe CAP) with the DDD of the antibiotics that would be prescribed based on the identified respiratory pathogen.FINDINGS: Empiric coverage recommended by IDSA/ATS resulted appropriate in 24.9%, insufficient in 2.4%, excessive in 57.6% and useless in 15.1%. Total antibiotic consumption for the included patients, according to identified pathogens, would be 2.255 DDD. Predicted antibiotic use based on IDSA/ATS guidelines would increase to 4.440 (97% more). The DDD raise was higher in moderate and severe categories compared to mild CAP (130%, 129.4% and 53.9%, respectively).INTERPRETATION: Implementation of IDSA/ATS 2007 guidelines for the treatment of CAP induces a considerable increase in antibiotic prescription, especially in moderate and severe cases. A judicious clinical assessment and better diagnostic tools should be used to optimize antibiotic therapy in CAP.FUNDING: This study was supported by research grant 1115- 04-16498 from Colciencias and University of Antioquia, Medellín, Colombia.